The Symbolic Management of Strategic Change: Sensegiving Via Framing and Decoupling - Fiss, Peer C.; Zajac, Edward J. (Academy of Management Journal, 2006)
This study develops a symbolic management perspective on strategic change to predict and test the antecedents and consequences of how firms frame strategic change. Using data from a sample of contemporary German corporations, we find support for our predictions that firms (1) use specific framing language that fits better with their divergent stakeholder preferences, (2) use language that decouples espousal and actual implementation of strategic change, and (3) realize positive market responses to institutionally appropriate frames of change.